Regional Autonomy and Governance Challenges: An Analytical Study on Policy Effectiveness - Bambang Irawan; Wildan Zaman; Tamaulina Br Sembiring; Arief Fahmi Lubis (Ipso Jure, 2025)
Regional autonomy in Indonesia aims to increase the efficiency and effectiveness of government administration through decentralization. However, its implementation still faces various challenges, especially in fiscal inequality, the quality of public services, and transparency and accountability of governance. Regional dependence on central transfer funds hinders financial flexibility, while disparities in human and administrative capacity exacerbate development inequality. Other obstacles include a sluggish bureaucracy, low use of information technology, and weak supervision of regional policies, which contribute to the rampant practice of corruption and maladministration. This study uses a normative juridical approach by analyzing Law Number 23 of 2014 concerning Regional Government as well as literature studies to evaluate the effectiveness of local government governance. The results of the study show that improving the fiscal transfer mechanism, optimizing Regional Original Revenue (PAD), digitizing services, and strengthening the supervision system and public participation are strategic steps in increasing the effectiveness of regional autonomy. Policy reform based on good governance and transparency is a key factor in creating an accountable and responsive local government to the needs of the community. With these steps, it is hoped that local governance in Indonesia can run more optimally and sustainably